Surgical correction of pulmonary veins draining into the left innominate vein - Aytaç, Aydın; Bilgiç, Arman; Saylam, Argun; Sarıoğlu, Tayyar; İkizler, Coşkun (The Turkish Journal of Pediatrics, 1981)
A rare case of partial anomalous pulmonary venous connection is presented where the left inferior pulmonary vein drained into the left atrium and all other pulmonary veins into the left innominate vein via a common pulmonary venous sac and a common pulmonary vertical vein. The patient was correctly diagnosed preoperatively, and the surgical intervention was performed by open heart technique. An anastomosis was performed between the common pulmonary venous sac and the left atrial appendix. The junction of the common pulmonary vein and the left innominate vein was ligated. The atrial septal defect (secundum) was closed by primary sutures. The absence of pulmonary hypertension in this case helped a great deal in the successful outcome of the operation.